France : the land and its people - Lifshitz, Danielle (London : Macdonald Educational ; Morristown, N.J. : S. Burdett, 1973)
An introduction to the people, history, culture, government, and geography of France.
Includes index.
Keywords: France -- Juvenile literature; France